Gene doping in modern sport - Cieszczyk, P.; Maciejewska, A.; Sawczuk, M. (Biology of Exercise, 2009)
Background: The subject of this paper is gene doping, which should be understood as "he non-therapeutic use of cells, genes, genetic elements, or of the modulation of gene expression, having the capacity to improve athletic performance". The authors of this work, based on the review of literature and previous research, make an attempt at wider characterization of gene doping and the discussion of related potential threats. Methods: This is a comprehensive survey of literature on the latest applications of molecular biology in medicine. The analysis involves a dozen scientific databases examined in order to find genes used in gene therapy and potentially useful in gene doping. Results: The obtained results enable better recognition of gene doping and indicate genes used in medicine that could be used in gene doping. This paper describes potential effects of their use and associated risk, and predicts the possible developments of gene doping in the future. Conclusion: Gene doping is undoubtedly a part of modern sport. Although WADA included gene doping on the list of banned methods as early as 2004, as previously stated above, it has not managed to develop efficient methods of detection.